Basil Fawlty as a ‘pre-Thatcherite’ Conservative in Fawlty Towers - Rami Mähkä (Intellect Ltd., 2022)
The article analyses the popular British situation comedy Fawlty Towers (1975, 1979) as a comedic representation of conservatism and its lead character, Basil Fawlty (played by John Cleese), as a ‘pre-Thatcherite’. The article discusses how the character of Fawlty can help us understand the processes that led to Margaret Thatcher winning the election in 1979 and becoming prime minister. Fawlty promotes similar values to Thatcher, but with ambiguity as the series is a comedy; comedy makes interpretation of ideological issues problematic as it is an alternative meaning-making system to non-comedic forms